2013
DOI: 10.1107/s1600536812051422
|View full text |Cite
|
Sign up to set email alerts
|

Di-μ-chlorido-bis[(2,2′-bipyridine-5,5′-dicarboxylic acid-κ2N,N′)chloridocopper(II)] dimethylformamide tetrasolvate

Abstract: Key indicators: single-crystal X-ray study; T = 100 K; mean (C-C) = 0.003 Å; disorder in solvent or counterion; R factor = 0.029; wR factor = 0.068; data-toparameter ratio = 16.4.In the title compound, [Cu 2 Cl 4 (C 12 H 8 N 2 O 4 ) 2 ]Á4C 3 H 7 NO, which contains a chloride-bridged centrosymmetric Cu II dimer, the Cu II atom is in a distorted square-pyramidal 4 + 1 coordination geometry defined by the N atoms of the chelating 2,2 0 -bipyridine ligand, a terminal chloride and two bridging chloride ligands. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…[17] Experimental Section Synthesis of H 2 bpydc-CuCl 2 H 2 bpydc-CuCl 2 was synthesized according to the literature. [18] 2,2bipyridine-5,5-dicarboxylic acid (H 2 bpydc) (40 mg, 0.16 mmol) and copper chloride dihydrate (60 mg, 0.35 mmol) were added into DMF (6 mL), and the mixture was heated until completely dissolved. Slow bench cooling to RT yielded the expected product.…”
Section: Resultsmentioning
confidence: 99%
“…[17] Experimental Section Synthesis of H 2 bpydc-CuCl 2 H 2 bpydc-CuCl 2 was synthesized according to the literature. [18] 2,2bipyridine-5,5-dicarboxylic acid (H 2 bpydc) (40 mg, 0.16 mmol) and copper chloride dihydrate (60 mg, 0.35 mmol) were added into DMF (6 mL), and the mixture was heated until completely dissolved. Slow bench cooling to RT yielded the expected product.…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons, multiple attempts were made to synthesize complexes of Cu(II) with two Cl ligands and either 2,2'-bipyridine (bpy) or H2bpydc as ligands, to be used as reference compounds for the XAS measurements. However, these were difficult to procure in the required quantity and purity, and the product was a mixture of polymorphs, or dimeric species as previously reported [96]. Another reference compound based on tert-butylbipyridine (tBbpyCuCl2) was hence chosen, and prepared as described in Section 2.1.…”
Section: Structural Determination Of the Tbbpycucl2 Model Compoundmentioning
confidence: 99%
“…There are several copper(II) dimeric compounds in which the copper atoms are bridged by chlorido ligands (Marsh et al, 1983;Puschmann et al, 2001;Li et al, 2006;Lee, et al, 2008;Han et al, 2008;Øien et al, 2013;Choubey et al, 2015;Golchoubian & Nateghi 2016;Liu et al, 2009). A search of the Cambridge Structural Database (Version 5.38, November 2016; Groom et al, 2016), revealed numerous di--chlorido bridged copper(II) compounds constructed with ligands having -N,O-donor atoms (Kapoor et al, 2002(Kapoor et al, , 2004Damous et al, 2013;Lumb et al, 2013;Smolentsev et al, 2014;Qureshi et al, 2016).…”
Section: Database Surveymentioning
confidence: 99%